Pengaruh Omnichannel Retailing terhadap Customer Retention melalui Customer Satisfaction dan Customer Engagement Dimoderasi Man Machine Collaboration - Husna El Wafa; Puspita Chairun Nisa (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This study analyzes the impact of omnichannel retailing on customer retention, focusing on customer satisfaction and engagement as mediators, and the role of man-machine collaboration as a moderator. Utilizing a quantitative approach and PLS-SEM on Sociolla customers, findings reveal that omnichannel retailing significantly enhances customer satisfaction and engagement but does not directly affect customer retention. Customer satisfaction positively influences retention, while engagement does not. The mediation analysis confirms customer satisfaction's role in linking omnichannel retailing with retention, while man-machine collaboration does not moderate this relationship. Overall, omnichannel strategies are most effective in boosting customer satisfaction, which indirectly supports customer retention.